Biological and Psychological Factors Associated With Smoking Abstinence Six Years Post-Stroke. Issue 10 (4th July 2017) - Suñer-Soler, Rosa; Grau-Martín, Armand; Terceno, Mikel; Silva, Yolanda; Davalos, Antoni; Sánchez, Juan Manuel; Font-Mayolas, Silvia; Gras, Eugenia; Rodrigo, Joana; Kazimierczak, Martha; Malagón, Carmen; Serena, Joaquín
Abstract: Introduction: Tobacco use is a public health problem causing high morbidity and mortality, including stroke. This study evaluates predictive factors of smoking cessation in the long term after stroke. Methods: We followed a cohort of 110 consecutive smokers with stroke for up to 6 years. Sociodemographic variables, stroke severity, insular involvement, stage of change in smoking habit before stroke and disruption of addiction variable (smoking cessation, absence of relapses, having stopped smoking without difficulties and not having had urge) were evaluated. Results: Twenty patients died during follow-up and two patients were lost leaving a final cohort of 88 patients. The prevalence of smoking cessation in the remaining population was 65.9% post-stroke, 54.9% at 3–6 months, 40.9% at 1 year and 37.5% at 6 years. Prevalence was significantly higher in patients with insular involvement during the first year of follow-up, but not at 6 years. Disruption immediately after stroke (OR = 10.1; 95% CI = 2.5 to 40.1) and intention to change before having the stroke (OR = 4.8; 95% CI = 1.0 to 23.0) were predictors of abstinence at 6 years after adjusting for age, sex and stroke severity at baseline. When tobacco abstinence at the 1 year follow-up was included in the model, this factor was the best predictor of tobacco abstinence at 1 year (OR = 10.5; 95% CI = 2.2 to 49.4). Conclusions: Intention of change, having the disruption criteria, and abstinence 1 year after stroke were predictors of abstinence at 6 years. An insular lesion in the acute phase of stroke does not determine the tobacco use status at 6 years. Implications: This study is the first prospective investigation with a cohort of stroke patients to examine the long-term influence of biological and psychological factors on smoking cessation. Tobacco abstinence 1 year after stroke was the strongest predictor of abstinence at 6 years of follow-up. The effect of the insular cortex lesion on tobacco cessation, which had been relevant during the first year, no longer had an influence over the longer period studied here.